EFFECTIVENESS OF ROSUVASTATIN IN VERY HIGH RISK CARDIOVASCULAR PATIENTS IN THE ACTUAL OUTPATIENT PRACTICE - V. P. Mikhin; D. V. Nebieridze; N. M. Akhmedzhanov; Yu. A. Zhilyaeva (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To evaluate the comparative efficacy of Rosivastatin (Rosart) and atorvastatin in patients with very high grade of cardiovascular risk (CVR), arterial hypertension (AH) and chronic ischemic heart disease (CHD) in outpatient practice.Material and methods. Totally, 2 groups studied, of patients with chronic CHD with AH (n=50) and isolated AH (n=50) with very high CVR by SCORE, had taken during 1 year the traditional antianginal, antihypertension therapy, and aspirin. Under the outpatient conditions, patients received atorvastatin 20 mg/day, that have not led to target lipid levels in blood. Atorvastatin was repaced by rosuvastatin (Rosart) 10 mg/day, for 1 year. In cases, when the dosage provided did not lead to cholesterol (Ch) decrease, and low density lipids cholesterol (LDL) to target levels for 6 weeks, Rosart dosage was increased to 20 mg/day: in 2% cases in CHD, in 8% in AH; in 8% cases Rosart dosage was increased to 40 mg/day for next 6 weeks.Results. Replacement of atorvastatin by rosuvastatin increased the efficacy of antihypertension treatment, decreased the need for sublingual nitroglycerin, decreased the rate of angina attacks, decreased the quantity of patients that did not reach target blood pressure (BP), decreased the rate of destabilizations of angina, rate of hospitalizations for cardiovascular events, number of hypertension crises and led, in most cases — with Rosart 10 mg/day, to achivement of target Ch and LDL levels, to decrease the vessel wall rigidity parameters, to increase the coefficient of endothelium dysfunction coefficient, that represents the rate of endothelium-dependent vasodilation, with absence of significant hepatotoxic and myopathic adverse events.Conclusion. The data obtained makes it to recommend the wider usage of Rosart in patients with very high CVR in outpatient practice.